PENEGAKAN HUKUM PERDAGANGAN SATWA LIAR (HEWAN KUKANG) DI WILAYAH KOTA BATU - Ferry Anggriawan (Esensi Hukum, 2024)
Indonesia, as a mega-biodiversity country, faces serious threats from the illegal wildlife trade, including the slow loris (Nycticebus spp.), a protected endemic primate. This study aims to examine law enforcement efforts against wildlife trafficking within the jurisdiction of the Batu Police Department in East Java, as well as the role of the East Java Natural Resources Conservation Agency (BBKSDA). Using an empirical juridical approach, the study analyzes law enforcement practices through a case study of slow loris trafficking uncovered by the Batu Police cybercrime unit. The findings indicate that the success in revealing the case was due to collaboration between law enforcement and BBKSDA East Java, despite ongoing challenges. These include internal obstacles such as limited human resources and budget constraints, as well as external factors like low public awareness and the existence of organized crime networks. This study recommends a multisectoral approach, institutional capacity building, and improved public literacy as essential strategies for conservation efforts and combating wildlife trafficking in Indonesia.